2021
DOI: 10.1155/2021/5552569
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Structural Parameters of Shape Memory Alloy Corrugated Gaskets on the Contact Pressure of Bolted Flange Joints

Abstract: Shape memory alloy corrugated gaskets (SMA-CGs) can adapt to fluctuating working conditions due to their pseudoelasticity (PE) and shape memory effect (SME), which make them excellent sealing components. In this study, the deformation mechanism of SMA-CGs was examined according to their structural properties under installation and operating conditions to establish an SMA-CG thermal-mechanical coupling model with the finite element analysis (FEA) method, which has been verified through experimentation. Based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…To calculate the deformation process of the bulges and pits on the surface of NiTi alloy and obtain the fluid medium leakage micro-channel of the NiTi alloy corrugated gasket, the deformation process was simulated and analyzed by ABAQUS. The material parameters of the NiTi alloy are shown in Table 1, and its constitutive model and UMAT subroutine refer to the literature [24].…”
Section: Leakage Rate Simulation Methods Based On Fluid-structure Int...mentioning
confidence: 99%
“…To calculate the deformation process of the bulges and pits on the surface of NiTi alloy and obtain the fluid medium leakage micro-channel of the NiTi alloy corrugated gasket, the deformation process was simulated and analyzed by ABAQUS. The material parameters of the NiTi alloy are shown in Table 1, and its constitutive model and UMAT subroutine refer to the literature [24].…”
Section: Leakage Rate Simulation Methods Based On Fluid-structure Int...mentioning
confidence: 99%
“…The paper [13] studied the corrugated gasket's capacity to handle changing load temperatures is greatly enhanced by the application of a shape memory alloy. This study found that the great influence of gasket thickness on leakage.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…The vibration failure time of a Fe-Mn-Si SMA bolt is seven times that of a common bolt, and the anti-loosening effect is remarkable (Zhou et al, 2014). SMA corrugated gaskets (SMA-CGs) can adapt to fluctuating working conditions, which make them excellent sealing components (He et al, 2021). SMA bolted connections can provide reasonable damping for frame structures under explosion loads (Weli and Vigh, 2021).…”
Section: Introductionmentioning
confidence: 99%